Computer aided diagnosis sensor integrated outdoor shirts for real time heart disease monitoring. (31st October 2017) - Park, Ji-Ae; Han, Hee-Jeong; Heo, Jin-Chul; Lee, Jong-Ha
Abstract: The typical method of monitoring arrhythmia is to use a body patch type sensor with a wet electrode. It has several problems caused by wet electrodes for long-term monitoring. Thus, a monitoring sensor integrated into clothes with a dry electrode is proposed. In this study, we develop a smart outdoor shirt equipped with a dry electrode electrocardiogram (ECG) sensor for a cardiac arrhythmia computer aided diagnosis system. The sensor can be inserted in a console close to the chest, charged, used to communicate wirelessly, and connected with a smartphone application. The ECG signals measured by the smart shirt indicated that 97.5 ± 1% of the signals could be measured in an immobile state and at least 85.2 ± 2% of the signals could be measured during movement. We propose a computer aided diagnosis system for detecting cardiac arrhythmia. It was determined through experiments that the system can detect arrhythmia with an accuracy of 98.2 ± 2%. This study suggests that smart shirt which can diagnose arrhythmia will provide information that can quickly recognize arrhythmia in daily life or exercise.